A documentation of jobs pursued by interior design graduates - Cortez, Karina Diana A.; Panganiban, Martha (2006.)
The purpose of this study was to list, collate and categorize the various jobs pursued by interior design graduates, in order to come up with data that would be useful to interior design students and fresh graduates. This was achieved through the conduct of a telephone survey on U.P. interior design graduates who graduated in the years 1987-2006. Many conclusions were drawn from the implementation of this study. It was concluded that U.P. interior design students were inclined to interior design after graduation, as the majority proceeded to take the interior design licensure board examination. Furthermore, as confirmed by this study, licensure defined the professional practice of interior design. On the other hand, the main reason why others opted not to take the examination was because they engaged in work immediately after graduation. The need for income, thus, became a factor in determining the jobs pursued by graduates, other than the degree from which one has graduated. Despite the inclination towards interior design of most, unexpected results revealed that majority of U.P. interior design graduates pursued ID-allied jobs, and less than twenty-five percent (25%) pursued the professional practice of interior design. Many reasons were given as to why these graduates pursued ID-allied and alternative jobs. Some attributed their chosen jobs to their inadequate technical know-how. However, the main reason for the pursuance of other jobs-in particular, design-related jobs-was due to the application of interior design knowledge on related fields. Thus, it was concluded that interior design graduates were not limited to the professional practice of interior design by the study of interior design, but rather, were accessible to other professions by it. This research also reflected parallel interests among interior design graduates in pursuing new job trends related to and unrelated to the field of interior design. The exploration of this study into various professions pursued by these graduates, not only provided information about the practice of interior design as a career, but also presented the wide range of choices interior design graduates can go into. Results showed that a foundation in interior design paved the way to a variety of opportunities.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Interior decoration -- Vocational guidance